MENINGKATKAN PENGUASAAN KOSAKATA PADA ANAK USIA DINI MELALUI METODE BERCERITA DI KB TUNAS HARAPAN DESA MBUWU - Siti Hadija Alaydrus (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Based on the author's observations, the problem in the subject of research is in KB Tunas Harapan, Mbuwu Village in the development of children's language, the teacher has used the storytelling method in the learning process. However, the implementation is still not optimal, this finds various problems in the application of learning methods that are not appropriate when teaching sometimes causes various problems such as the lack of student participation in learning in class. While the objectives to be achieved in this study are how to improve vocabulary mastery in early childhood through the storytelling method in KB Tunas Harapan, Mbuwu Village. The data analysis was carried out in 3 (three) stages, namely (1) data preparation, (2) data processing, (3) data presentation by focusing on the development of early childhood language associated with the storytelling method used by teachers in the classroom. To obtain data, the researcher used descriptive qualitative methods, observations, and interviews. The results of the study prove that the use of the storytelling method is optimal enough to develop the language development of children in KB Tunas Harapan, Mbuwu Village in its implementation, it can be seen from the results of research that have been achieved by students of KB Tunas Harapan Mbuwu